2002
DOI: 10.1590/s1413-86702002000600008
|View full text |Cite
|
Sign up to set email alerts
|

Post-kala-azar dermal leishmaniasis associated with AIDS

Abstract: Post-kala-azar dermal leishmaniasis (PKDL) is rarely reported in South America. In spite of the fact that there are many reports about the association of visceral leishmaniasis and AIDS, PKDL is very uncommon in HIV-positive patients, and so far only four cases have been documented in the literature. We present another case with unusual clinicopathological aspects. The patient, a 28-year-old male, from Salvador, Bahia (an endemic area) presented with clinical manifestations of visceral leishmaniasis three year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…N ew World cutaneous leishmaniasis, caused by Leishmania braziliensis (Lb), 3 is distinguished from other leishmaniasis by its chronicity, latency, and tendency to metastasize in the human host (1). During infection with Lb, development of clinical lesions coincides with an influx of inflammatory cells such as macrophages, eosinophils, and neutrophils (2,3).…”
mentioning
confidence: 99%
“…N ew World cutaneous leishmaniasis, caused by Leishmania braziliensis (Lb), 3 is distinguished from other leishmaniasis by its chronicity, latency, and tendency to metastasize in the human host (1). During infection with Lb, development of clinical lesions coincides with an influx of inflammatory cells such as macrophages, eosinophils, and neutrophils (2,3).…”
mentioning
confidence: 99%
“…The nested PCR assay used in the present study circumvented such limitations and showed a high degree of sensitivity even in macular cases. Cases of PKDL infection in patients with human immunodeficiency virus (HIV) have been reported (1,7). Since the incidence of HIV infection is on the increase in India, HIV patients coinfected with Leishmania are likely to present in the future.…”
mentioning
confidence: 99%
“…29 PKDL is thought to be uncommon in HIV/AIDS patients and so far only a few cases of PKDL in HIV-positive patients have been reported from other foci. 4,[40][41][42] However, in Ethiopia, PKDL is reported to be more common in HIV-positive patients than in HIV-negative VL patients. 43 This finding is controversial but severity of immunosuppression in these patients is unknown because CD4 cell counts were not reported.…”
Section: Discussionmentioning
confidence: 99%